Teacher Development from the Perspective of an English Teacher: A Narrative Inquiry - Refi Aksep Sativa; Fnu Meilani; Harry Ramadan Putra; Eri Kurniawan (Indonesian TESOL Journal, 2022)
Teacher development (TD) has become an essential pathway for teachers to develop themselves and their teaching, and to enhance their students’ achievement. This study examines a relatively new area that has emerged from the growing body of teacher development literature. It focuses on a teacher’s perceptions and beliefs regarding teacher development values, specifically in five sub-components: teacher development as a moral process; teacher research values; career development values; marginality and advocacy values; and teacher education values in English language teaching. Semi-structured interviews were conducted to explore the participants’ views on, and experiences of, the topics. The data analysis employed an interactive model consisting of data collection, display, condensation, and conclusion-drawing. The results indicate that the teacher undergoes specific teaching and learning processes within each component, contributing to his belief in teacher development. This study also recommends that solid communication and collaboration among teachers, students, and officials lead to a better quality of education.